The Effect of Juice Ratio of Passion Fruit With Papaya and Sugar Concentration on Hard Candy Quality - Tri Wahyuni; Linda Masniary Lubis; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The purpose of this study was to determine the effect of passion fruit ratio with papaya and sugar concentration of the quality of hard candy. Method of this study was randomized complete design with two factors, ratio of passion fruit and papaya (T) (50% : 50%, 60% : 40%, 70% : 30%, 80% : 20%) and sugar concentration (M) (40%, 50%, 60%, 70%). The analyzed parameters include moisture content, ash content, ascorbic acid content, total acid, total soluble solid, sensory test (color, flavor, taste and texture).The ratio of passion fruit and papaya gave a significant different effect on moisture content and gave significant different effect on ash content, ascorbic acid content, total acid, total soluble solid, sensory test (color, flavor, taste and texture). The sugar concentration gave a significant different effect on moisture content, ash content, ascorbic acid content, total acid, total soluble solid, sensory test (color, flavor, taste and texture). The interaction of the passion fruit ratio with papaya and sugar concentration had no significant different effect on moisture content, ascorbic acid content, total acid, total soluble solid, sensory test (color, flavor, taste and texture) but gave a significant different effect on ash content. The best composition which gave the best effect on hard candy is 80% : 20% of passion fruit ratio with papaya and 70% of sugar concentration. Keyword : Hard candy, papaya, passion fruit, sugar concentration.